Between Reason and Irrationality - Tarnawsky, Maxim (Book collections on Project MUSE., 1994)
From the earliest stories of the seventeen-year-old writer, whose focus was on the psychology of sexuality, to the last known work, which recounts a hopeless quest for an unattainable goal, Pidmohyl'nyj's works are linked by a variety of philosophical and aesthetic threads. Chief among these is his interest in the fundamental duality of human beings, their disharmony as both physical creatures driven by natural needs and desires, and rational beings. This conflict between instinct and intellect, irrationality and reason, is the central focus of all Pidmohyl'nyj's writings and Tarnawsky's primary subject.